2020
DOI: 10.1002/ps.5960
|View full text |Cite
|
Sign up to set email alerts
|

Novaluron prevents oogenesis and oviposition by inducing ultrastructural changes in ovarian tissue of young adult Lygus lineolaris

Abstract: BACKGROUND: The tarnished plant bug, Lygus lineolaris (Palisot de Beauvois), has emerged as a major pest of cotton, Gossypium hirsutum L, in the mid-southern USA. In the early 1990s L. lineolaris populations developed resistance to several classes of conventional insecticides, increasing the need for insecticides with alternative modes of action such as insect growth regulators (IGRs) for integrated pest management (IPM). The benzoylphenyl urea (BPU) class of IGRs acts by disrupting the growth and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Studies performed in the laboratory by Tail et al (2010) with the grasshopper S. gregaria, to verify the influence of the ingestion of diflubenzuron (30 mg/ml), the authors found reduced weight of the ovaries after females of this species ingested this IGRs. In a study with adult of Lygus lineolaris (Palisot Beauvois, 1818) (Heteroptera: Miridae), which ingested a diet incorporated with novaluron (600 ppm), Catchot et al (2020) observed a negative effect on oviposition rate, ovarian maturation, and hatching of eggs laid by this species. These results corroborate those obtained in this work when adults of E. heros were exposed to soybean leaves treated with novaluron at the highest dose tested, for egg viability, although the target species and exposure mode were different.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in the laboratory by Tail et al (2010) with the grasshopper S. gregaria, to verify the influence of the ingestion of diflubenzuron (30 mg/ml), the authors found reduced weight of the ovaries after females of this species ingested this IGRs. In a study with adult of Lygus lineolaris (Palisot Beauvois, 1818) (Heteroptera: Miridae), which ingested a diet incorporated with novaluron (600 ppm), Catchot et al (2020) observed a negative effect on oviposition rate, ovarian maturation, and hatching of eggs laid by this species. These results corroborate those obtained in this work when adults of E. heros were exposed to soybean leaves treated with novaluron at the highest dose tested, for egg viability, although the target species and exposure mode were different.…”
Section: Discussionmentioning
confidence: 99%
“…The success of this approach is likely due to migrating adults being controlled before economic damage from feeding and extensive egg lay occurs. Control of local nymph populations hatching while there was residual novaluron and the potential reduced fecundity of remaining tarnished plant bug adults by the IGR proved beneficial (Catchot et al 2020). This strategy could prove useful in breaking the initial early season buildup of tarnished plant bugs moving into flowering cotton fields, which are most susceptible to yield loss (Wood et al, 2016).…”
Section: Subsequent Insecticide Treatmentmentioning
confidence: 99%
“…Data from Catchot et al (2021) indicated that ingestion of novaluron by tarnished plant bug adults was more effective than contact exposure; however, contact with treated foliage up to one day after application often led to the same result: decreased nymph populations. When adult females of any age were exposed to novaluron, reduced egg viability was observed in addition to ovarian malformation in newly reproducing adults (Catchot et al, 2020). Laboratory studies conducted by Owen et al (2011) showed that novaluron is more active against first instar nymphs as compared to second and fifth instars.…”
mentioning
confidence: 99%
“…Novaluron is an insect growth regulator that only affects the immature stages of L. lineolaris [ 164 ]. However, recent research has shown that novaluron can cause ultrastructural changes in the ovarian tissues of adult L. lineolaris that prevent oogenesis and oviposition [ 165 ]. Those sublethal effects have also been shown to reduce L. lineolaris populations in the field [ 166 ].…”
Section: Integrated Management Strategiesmentioning
confidence: 99%